Republic of Latvia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2005)
This Selected Issues paper seeks to determine the macroeconomic effects of credit growth in Latvia. To do so, the paper relies on two approaches. First, a vector autoregressive system consisting of domestic credit, real activity, inflation, and the current account is used to determine responses to a positive shock to credit growth. It also calibrates the IMF's Global Fiscal Model to simulate the macroeconomic effects of Latvia's financial integration with the European Union and developing financial system. The paper also discusses the balance sheet approach to macroprudential vulnerabilities in Latvia.